Principles of microwave measurements - Bryant, G. H. (London, United Kingdom : Pete Peregrinus on behalf of the Institution of Electrical Engineers,Ltd., 1988)
This book is aimed at the postgraduate or final-year honours level, and assumes some knowledge of electromagnetic theory and a general familiarity with microwave components. It should be useful to young engineers, who inevitably bear the burnt of detailed laboratory work, but also to more experienced engineers wishing to update or refresh their knowledge.
1. Swept-frequency principles -- 2. Error models -- 3. The Smith chart -- 4. Signal generation -- 5. Vector analysers -- 6. Scalar analysers -- 7. Six-ports -- 8. Power measurement -- 9. Noise -- 10. Frequency stability and measurement -- 11. Time-domain reflectometry -- 12. Antenna measurements
Keywords: ELECTRICAL ENGINEERING